What have we learned about antinociceptive effect of botulinum toxin type A from mirror-image pain models?. (15th October 2020) - Drinovac Vlah, Višnja; Bach-Rojecky, Lidija
Abstract: Mirror pain represents pain with complex pathophysiological background experienced at both sides of the body, usually after unilateral injury. Although observed almost 10 years ago, the phenomenon of bilateral antinociceptive effect of botulinum toxin type A (BoNT/A) following its unilateral administration in experimental mirror-image pain (MP) models remains challenging and intriguing task to explain. Data generated so far using MP models and mechanisms behind this unique feature of BoNT/A might influence the overall understanding of its mechanism of antinociceptive action. Here we review the effects contributing to BoNT/A's bilateral antinociceptive action observed in experimental MP models.